Start now, activate places: a guide to transforming public space with community-led event programs - Kappelman, Julia (Kansas State University, 2021)
The planning for amenities and events in parks and public space has long been used as a tool for attracting desired demographic groups and for pushing other populations out (Wangro 2018). Although landscape architects have the design background to create usable and successful public spaces, if they do not engage the local community in the process, there can be a lack of relevance in the end result. But what would happen if the typical roles of the designer and the community were switched? If the community could lead the event programming process and decide what a space needs, then the designer could help facilitate and offer suggestions. The research question asks, “How can a community-driven, participatory process create relevant, well-informed, and customized event programming in parks and public spaces to better serve the needs of their community?” To answer this research question, this project uses interviews, precedent studies, and a projective design as methods to inform the final outcome. The outcome is an event program guide, called the SNAP Guide, that community groups and leaders can use to inform the creation of relevant, informed, and customized event programs for their parks and public spaces. Through the use of the SNAP Guide, community groups and leaders can transform parks and public places through event programs that are relevant, well-informed, and customized through a community-led, participatory approach.
Keywords: Programming; Placemaking; Community engagement; Event programs; Landscape architecture